Integrated frailty and intrinsic capacity care model for community-dwelling older adults in Singapore: a rapid qualitative study of anticipated implementation barriers and enablers using the Consolidated Framework for Implementation Research and its Outcomes Addendum - Ginting, Mimaika Luluina; Sum, Grace; Wang, Sinead Zhen; Ding, Yew Yoong; Tay, Laura (Frontiers in Health Services, 2025)
IntroductionOlder adults are at increased risk of experiencing multimorbidity and care dependency due to declines in their physiological reserves. Optimizing the intrinsic capacity and functional ability of individuals is important to enable healthy aging. We engaged potential implementers of an integrated, community-based model for frailty and intrinsic capacity care, adapted from the World Health Organization Integrated Care for Older People framework, to assess the anticipated barriers and enablers to implementation within Singapore's healthcare context.MethodsThe updated Consolidated Framework for Implementation Research (CFIR) and its Outcomes Addendum was adopted as the conceptual framework. Qualitative data were collected through focus group discussions (FGDs). We used a rapid qualitative inquiry approach, incorporating a combination of Rapid Research, Evaluation and Appraisal Lab sheet, the Rapid Identification of Themes from Audio recordings, and mind-mapping techniques for data synthesis, analysis, and interpretation. The framework approach was applied to structure and explore the qualitative data for triangulation across FGDs.ResultsFive FGDs were conducted with 22 potential implementers (doctors, nurses, physio/occupational therapists, and community partners) between July and August 2023. We identified 24 CFIR determinants covering five domains (innovation, outer setting, inner setting, individuals, and implementation process). Enablers included intersectoral collaboration (partnership and connections), trialability (innovation trialability), alignment with overarching goal (mission alignment), and removal of hurdles and sufficient support (tailoring strategies). Barriers included complexity (innovation complexity), affordability (innovation cost), tradeoffs (relative priority), synergy among multiple programs (compatibility), resource intensity (available resources), fragmented understanding of the care model across providers (communication), physical spaces' design (physical infrastructure), limited time and resources (innovation deliverers' opportunity), gaps in clients' capability (capability), and non-compliance (motivation). Policy contexts and directives (policies and laws), theoretical benefits (innovation evidence base), comprehensiveness and patient-centeredness (design), enhanced service access (relative advantage), proposed task allocation (work infrastructure), information access (information technology infrastructure), capability building (access to knowledge and information), innovation deliverers' capability, motivation, and accessibility (innovation recipients' opportunity) were both barriers and enablers.DiscussionThe findings demonstrated agreement with the innovation and suggested implementation readiness at clinical and service levels. However, addressing key barriers and leveraging existing enablers are necessary for successful adoption and implementation.